Clinical spectrum of COVID-19 at a national referral hospital in western Kenya during the period 2020–2021 - Ogalo, Edith A.; Gudu, Edwin; Andale, Thomas; Korir, Daisy; Ndege, Samson; Simiyu, Tabu; Olekuyo, Richard; Mwangi, Henry; Kimaiyo, Sylvester; Aruasa, Wilson (Frontiers in Virology, 2023)
Introduction We describe the clinical spectrum of COVID-19 cases in western Kenya from 6 April 2020 to 31 May 2021, providing baseline data for further studies into COVID-19 in Kenya. Methods We did a retrospective chart review of laboratory and inpatient files of patients diagnosed and managed for COVID-19 at the Moi Teaching and Referral Hospital in Kenya and analyzed the data using Stata® version 16 (StataCorp LP, College Station, TX, USA) and calculated measures of association at 95% CI. Results The patients (n = 1,770) had a mean age of 43 years (SD 20 years) and 55.4% were male. Close to 70% had asymptomatic disease, with the symptomatic cases largely being respiratory in nature. One-quarter had comorbidities. The case fatality rate was 13.6% (n = 240). Male sex increased the odds of mortality by 1.69 (95% CI 1.27–2.25; p ≤ 0.001), and the presence of comorbidities increased the odds of mortality by 3.16 (95% CI 2.38–4.18; p ≤ 0.001). Those aged 59 years and above were 18 times more likely to die from COVID-19 than those below 15 years of age (95% CI 1.61–90.66; p = 0.015). Conclusion COVID-19 had a significantly high mortality rate in western Kenya. Male sex and the presence of comorbidities increased the risk of severe disease and mortality.